Sistem Pendukung Keputusan Pemilihan Media Chatting Terbaik Menggunakan Metode MAUT - Mochamad Dedy Subekti Rahardjo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of technology is increasingly widespread so that it can make it easier for us to carry out all activities / activities. For example, such as communicating even though they are far away. By using media which is now very rapidly developing, the media are Whattsap, Instagram, Facebook and so on, but in the selection of chat media there is often confusion because there are too many features contained in the chat media. so in this study there are 5 criteria including Storage Media, Security, Application Features, Appearance / Interface, and Network Data Usage. So that in solving this problem, a decision support system is needed with the help of a method to get a fast and accurate final result. So in this study, with the title of selecting the best chat media, the best ranking results were found in A2, the name of the media Instagram with a total value of 0.1623.